Adsorptive removal of lead from acid mine drainage using cobalt-methylimidazolate framework as an adsorbent: kinetics, isotherm, and regeneration - Nqombolo, Azile; Mpupa, Anele; Gugushe, Aphiwe S.; Moutloali, Richard M.; Nomngongo, Philiswa N. (Environmental science and pollution research international, 2019)
In this work, cobalt-methylimidazolate framework has been used as an adsorbent in the removal of Pb(II) from acid mine drainage in adsorption batch system. X-ray diffraction, Fourier-transform infrared spectroscopy, Brunauer-Emmet-Teller and transmission electron microscope were used for structural, morphological, and surface characteristics of cobalt-methylimidazolate framework. The concentration of heavy metal ions in water samples was measured by inductively coupled plasma optical emission spectrometry. Different experimental factors/variables (such as contact time, dosage, and pH) affecting the adsorption of Pb(II) from acid mine drainage were optimized by response surface methodology based on central composite design. Under optimized experimental parameters, the maximum adsorption capacity of Pb(II) was found to be 105 mg g −1 . The nature of the adsorption process was investigated using Langmuir and Freundlich isotherm models. The obtained data best fitted Langmuir isotherm model suggesting a homogeneous adsorption process. Furthermore, the adsorption mechanism was investigated using five kinetic models, that is, pseudo-first order, pseudo-second order, intraparticle diffusion and Elovich model. The adsorption data fitted better to pseudo-second-order followed by intra-particle diffusion kinetic models suggesting that the adsorption mechanism is dominated by both chemical and physical adsorption processes. The adsorbent could be regenerated up to 8 cycles and it was successfully used in the removal of lead in real acid mine drainage samples.